Construção e gestão de marcas próprias no grande varejo supermercadista brasileiro: um estudo de caso - Almeida, Carla Aparecida de Sousa (2010)
Retail is considered one of the main econimic forces in Brazil, responsible for more than 10% of Brazilian GDP. Along with social, cultural, economic and technological changes happened over the last years, the retail sector has suffered significant changes and the companies in this segment are still adapting themselves to new demands of marketing and consumers, and also to an even more competitive scenario that has required from the players to develop strategies to stand up to competitors. In the retail, specially the supermarkets, one of these strategies is to introduce private label products into their businesses, although the branding process of these kind of brands or supermarkets corporate brands are new, even regarding to the relevance of the subject that is growing over the years on academic and marketing studies. Despite in Brazil private labels detain lower share rates than European countries 7% against 46% in Switzerland, these brands products consumption are gradually growing as well as its consumer s approval. It means there is potential to its development and the supermarket trade has invested over and over in these products and branding improvement, what motivates this study structured to identify and analyze the building process and management of private labels in this market segment. In order to achieve the present objective it was decided by case study method analyzing the Grupo Pão de Açúcar private labels, making use as concept basis the brand leadership model proposed by authors David A. Aaker and Erich Joachimsthaler. The study showed the process adopted by the Company in private labels building and management converging mostly to the proposed practices suggested by the referential model, and that these brands have strategic role to the organization considering the constants initiatives performed by Grupo Pão de Açúcar